Pengaruh Penerapan Model Pembelajaran Problem Based Learning (PBL) Terhadap Kemampuan Berpikir Kritis Dan Self Confidence Siswa - Fachri Awami; Syamsuri Syamsuri; Yuyu Yuhana; Hepsi Nindiasari (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2022)
This study aims to determine the effect of students' self-confidence and mathematical critical thinking skills of students who are taught with the Problem Based Learning (PBL) learning model with conventional learning. The research design used in this study was the Nonequivalent (pretest-posttest) Control- Group Design which was carried out in the odd semester of the 2021-2022 academic year at SMK Negeri 13 Pandeglang. Data was collected using pretest and posttest. Hypothesis testing is done by using a t test. The results of data analysis showed that sig. > 0.05 means that the remaining mathematical critical thinking skills and self-confidence of students taught by the PBL learning model are better than the mathematical critical thinking skills and self-confidence of students taught by conventional learning. The contribution of the PBL learning model to the improvement of critical thinking skills is 43% and to the increase in students' self-confidence by 58% compared to conventional learning.